HUBUNGAN ANTARA PENGGUNAAN GAWAI DENGAN NOMOPHOBIA PADA SISWA KELAS XI IPS DI SMA NEGERI 4 SINGARAJA - Komang Mia; Komang Yogi Triana; Ni Made Ari Sukmandari (LPPM STIKes Buleleng, 2023)
ABSTRACT Introduction: Gadgets are electronic devices and communication tools that are most popular in this era. The use of gadgets has become a habit, especially the high use of gadgets that are not limited in time limits is likely to cause dependence and symptoms of nomophobia, nomophobia which is anxiety, fear and even discomfort when someone is away from their gadgets. The purpose of this study was to determine the relationship between gadget and nomophobia in Social Science Program of Class XI Students at SMAN 4 Singaraja. Method: This study used a descriptive analytic design with a cross sectional approach with the variables measured were the use of gadget and nomophobia. The sampling technique was purposive sampling with the number of samples used amounted to 82 respondents. Data collection using device usage questionnaire and NMP-Q. Univariate analysis is displayed in the form of a frequency table and bivariate analysis is done with the spearman rank test. Result: The results of this study showed that the use of devices in the high category was 69 people (84.1%) and the low category was 13 people (15.9%). For the level of nomophobia, 5 people (6.1%) experienced low nomophobia, 34 people (41.5%) experienced moderate nomophobia and 43 people (52.4%) experienced high nomophobia. This shows that there is a relationship between the use of gadgets and nomophobia in class XI social studies students at SMA Negeri 4 Singaraja with a p value = 0.002 (Î± < 0.05). Conclusion: Students should be wiser and be able to control themselves and the time in using gadgets so that they do not experience dependence or nomophobia, therefore use